Untold Histories of the Middle East: Recovering Voices from the 19th and 20th Centuries - Singer, Amy; Neumann, Christoph K.; Somel, Selçuk Akṣin (SOAS/Routledge Studies on the Middle East, 2011)
Much traditional historiography consciously and unconsciously glosses over certain discourses, narratives, and practices. This book examines silences or omissions in Middle Eastern history at the turn of the twenty-first century, to give a fuller account of the society, culture and politics. With a particular focus on the Ottoman Empire, Turkey, Egypt, Iran and Palestine, the contributors consider how and why such silences occur, as well as the timing and motivation for breaking them. Introducing unexpected, sometimes counter-intuitive, issues in history, chapters examine: women and children survivors of the Armenian massacres in 1915 Greek-Orthodox subjects who supported the Ottoman empire and the formation of the Turkish republic the conflicts among Palestinians during the revolt of 1936-39 pre-marital sex in modern Egypt Arab authors writing about the Balkans the economic, not national or racial, origins of anti-Armenian violence the European women who married Muslim Egyptians Drawing on a wide range of sources and methodologies, such as interviews; newly-discovered archives; fictional accounts; and memoirs, each chapter analyses a story and its suppression, considering how their absences have affected our previous understandings of the history of the Middle East. Amy Singer is Professor of Ottoman history at Tel Aviv University. Her research focuses on the Ottoman public kitchens ( imaret ), and on the city of Edirne. She won the 2008 Sakıp Sabancı International Research Award in Turkish Studies for 'The Persistence of Philanthropy'. Christoph K. Neumann is chair of Turkish Studies at Ludwig Maximilian University Munich. He has published widely on Ottoman history. He did research and taught at the Orient-Institute in Istanbul, in Prague and again at different universities in Istanbul. Selçuk Akşin Somel is Assistant Professor of Ottoman History at Sabanci University, Turkey. He specializes in Ottoman education, gender history, legitimacy and power, and peripheral populations. He previously taught at Freiburg University, and Bilkent University, Ankara. Introduction: ReSounding Silent Voices Selçuk Akşin Somel, Christoph K. Neumann, and Amy Singer Part I: Missing Women 1. Unraveling Layers of Gendered Silencing: Converted Armenian Survivors of the 1915 Catastrophe Ayşe Gül Altınay and Yektan Türkyılmaz 2. Interfaith Unions and Non-Muslim Wives in the Early Twentieth-Century Alexandria Islamic Courts Hanan Kholoussy 3. The Silence of the Pregnant Bride: Non-Marital Sex in Middle Eastern Societies Liat Kozma Part II: Marginal Lives 4. Silent Voices within the Elites: The Social Biography of a Modern Shaykh Yoav Alon 5. A Nationalist Discourse of Heroism and Treason: The Construction of an "Official" Image of Çerkes Ethem (1886-1948) in Turkish Historiography, and Recent Challenges Bülent Bilmez 6. On the Margins of National Historiography: The Greek İttihatçi Emmanouil Emmanouilidis – Opportunist or Ottoman patriot? Vangelis Kechriotis 7. The Ottoman Empire's Absent Nineteenth Century: Autonomous Subjects Christine Philliou 8. Looking Behind Hajji Baba of Ispahan: The Case of Mirza Abul Hasan Khan Ilchi Shirazi Naghmeh Sohrabi Part III: Memories of Conflicts 9. Between the Balkan Wars (1912-13) and the "Third Balkan War" of the 1990s: The Memory of the Balkans in Arabic Writings Eyal Ginio 10. The Courts of the Palestinian-Arab Revolt, 1936-1939 Mustafa Kabha 11. Multiplicity or Polarity: A Discursive Analysis of post-1908 Violence in an Ottoman Region Meltem Toksöz